Multiple biomarkers in pufferfish as a proxy of environmental health in brazilian marine protected areas - Marinsek, Gabriela Pustiglione [UNESP]; de Oliveira, Isabelly Cristina Correia dos Santos [UNESP]; Ribeiro, Caio César [UNESP]; Gusso-Choueri, Paloma Kachel; Choueri, Rodrigo Brasil; Abessa, Denis Moledo de Souza [UNESP]; Mari, Renata de Britto [UNESP] (Elsevier, 2024)
Marine Protected Areas (MPAs) are designed to conserve biodiversity and vulnerable ecosystems. This study aimed to assess the environmental quality of three Brazilian MPAs, based on the integrated analysis of biomarkers in pufferfish. The MPAs are differentiated by the degree of anthropogenic influences. The Barra do Una Estuary sustainable reserve (JUR) is a reference area due to its low levels of contamination and species diversity. The Cananéia Estuarine System (CAN) has been recognized as a biosphere reserve by UNESCO, as well as a Ramsar wetland. This MPA was influenced by upstream mining activities, resulting in the introduction of metals in the estuarine waters and the discharge of untreated urban sewage. The São Vicente estuary (SSV) lacks proper sanitation infrastructure. All collections were conducted during winter season, and, after collection, the animals were euthanized, their soft tissues were removed, and multiple biomarkers were analyzed in the gills and liver, as biometric, genotoxic, biochemical, and morphological. A one-factor multivariate analysis was applied to evaluate the differences between the data sets, and the matrices were analyzed using PERMANOVA to evaluate the “estuary” factor. The results were integrated using PCA with a 0.4 cut value and an Enhanced Integrated Biomarker Response (EIBR) was calculated. PCA was correlated with biochemical, genotoxic, and morphological biomarkers. In general, SVV differed from CAN and JUR as shown by both univariate and multivariate analyses. SVV also showed the highest EIBR, followed by CAN. Organisms from SSV showed greater gill pathology, elevated AChE activity and lipoperoxidation (LPO), and micronuclei frequency. CAN present intermediate EIBR, with severe pathologies in the liver. CAN seems to present an intermediate environmental quality between SSV and JUR indicating the importance of the existence of MPAs for environmental conservation and the need to monitor such areas, to maintain their suitable environmental quality.
Keywords: Environmental quality assessment; Estuary; Fish; Gills; Liver